PEMANTAPAN NILAI-NILAI KEBANGSAAN BAGI ETNIS TIONGHOA - Kurnia Setiawan; Ninawati Lihardja; Meiske Yunithree (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
Pancasila values need to be understood and practiced in everyday life. The INTI (Indonesian Chinese) Association conducts training on